Kelp-stone ratio and bed roughness control green gravel stability under hydrodynamic forces - Maike Paul; Nils B. Kerpen; Armin Moghimi (PLoS ONE, 2026)
Kelp forests play a crucial role in marine ecosystems, providing habitat, food, and shelter for a variety of marine organisms. However, these ecosystems are facing significant threats, prompting the need for effective restoration strategies. One promising method is the use of “Green Gravel”, where kelp spores are cultivated on small stones for subsequent deployment in the ocean. The success of this method strongly depends on the kelp attaching firmly to the ground before the kelp-stone systems get displaced to unsuitable locations by hydrodynamic forcing. Here we systematically quantified the hydrodynamic and bed conditions leading to initiation of motion of kelp-stone systems in the laboratory. For full control on kelp dimensions, surrogates were used. Critical shear stress negatively correlated with kelp size, and bed roughness had a stronger influence on the initiation of motion than stone dimensions or bed slope. We introduce the Shields parameter with a stability correction, highlighting its strong correlation with kelp frontal area and stone diameter, and providing a powerful unifying metric for predicting the onset of movement under diverse conditions. Additionally, subtle movement of the kelp-stone systems prior to displacement was observed, potentially preventing attachment even at hydrodynamic conditions below the thresholds for initiation of motion. Understanding the mechanistic processes leading to motion of kelp-stone systems helps to improve restoration methods and thus contributes to the broader objectives of marine habitat conservation.